Fluorinated lanthanide complexes : new NIR-VIS upconversion systems - Bogdanov, Viktor (2018)
Lanthanide-based upconversion is a well-known process in solids, but for a wide variety of applications small size, preferentially molecular size upconversion emitters are required. Using inorganic upconversion nanoparticles solves some of the problems, however, the luminescence is severely quenched for smaller particle sizes. On the other hand, organic lanthanide complexes provide better overall luminosities and can be easily modified for medical applications, but rarely provide adequate quantum yield of NIR emission to enable upconversion processes. This work was aimed to realize conventional for inorganic systems Yb-Tb/Er upconversion in the perfluorinated organic complex and study its mechanism in order to explore the limits of the system and evaluate the perspective pathway. Green Yb-Tb upconversion by cooperative energy transfer (CET) mechanism was realized in vacuum, and green/red Yb-Er upconversion by energy transfer (ETU) mechanism was shown to be possible in ambient conditions for organic complex powder. Energy transfer pathways were studied in detail to explain features of the mechanisms, such as three-photon red upconversion for the latter case. Based on this data the conclusion about the perspectives is drawn and the outlook of the future work in the field is provided.